Characteristics of Adolescent Sexting: Results from the 2015 National Survey of Sexual Health and Behavior. Issue 8 (17th November 2019) - Beckmeyer, Jonathon J.; Herbenick, Debby; Fu, Tsung-Chieh (Jane); Dodge, Brian; Reece, Michael; Fortenberry, J. Dennis
Abstract: Using data from 78 sexting-experienced adolescents from the 2015 National Survey of Sexual Health and Behavior, we describe sexting frequency, sexting partners, sexual relationships with such partners, and characteristics associated with sexting. Most (59.2%) respondents sexted at most monthly, usually with romantic partners (62.0%). About 41% of sexting-experienced adolescents did not usually have sexual relationships with sexting partners, 36.6% usually sexted after starting a sexual relationship, and 16.8% reported that their sexting typically preceded sexual relationships. Younger adolescents sexted more frequently. Those without vaginal sex/anal sex experience, or prior romantic experience, were more likely to have sexted a non-romantic/sexual partner.